Los temas sociales en la integracion regional - Tizon, Allan Wagner (SELA CaracasVE, 1996)
Posits that the integration process can help to resolve social development problems in member countries; and, that the common norms that are necessary to adopt within an integration scheme, are inherent aspects of the process.